Who Will Choose the End Words? Structuring Justice Amid Tragedy - Brenda Waugh (Washington University Journal of Law & Policy, 2011)
The Article focuses on the restorative justice response to the 2007 Virginia Polytechnic Institute and State University (Virginia Tech) shooting by Seung-Hui Cho. Information is provided on the financial compensation award fund comprised of donations provided to victims and families. The author offers an examination of the shooting victims' rights to compensation.
Keywords: Restorative justice; Criminal justice administration; Compensation (Law); Damages (Law); Virginia Tech Shootings; Blacksburg; Va.; 2007; Seung-Hui Cho; 1984-2007